Scientific ethical approach to double effect or only possible good in therapeutic abortion - Valenzuela, Carlos Y. (Acta Bioethica, 2016)
This study shows the inapplicability of the doctrine of double effect (DDE) to all the cases of therapeutic abortion (TA). The causes of the maternal risk define cases that cannot be included in the DDE. When it is not the embryo or fetus that produces the mother pathology the case can be assigned to the DDE. When the embryo or fetus produces directly or indirectly the process that threatens the mother’s life the case cannot be assigned to the DDE. If the fetus is the cause of the imminent mother’s death, the removal of the cause, that is the proper therapy, coincides with killing him or her; then the good action (to save therapeutically the mother) is the same to the bad action (to kill the fetus) and this situation cannot be assimilated either to the DDE or to the doctrine of the lesser evil. Deciding not to kill the fetus will produce the death of the mother and the fetus. So this situation should be ascribed to the principle of the unique possible well.